2022
DOI: 10.1177/21925682221083913
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Validation of the Spine Oncology Study Group Outcomes Questionnaire in Italian Language

Abstract: Study design Prospective observational study Objective The population of patients with advanced stages of cancer, including metastatic spinal disease, is growing because of better treatment options allowing for longer control of disease. The main goal of treatment for these patients is to improve or maintain their health-related quality of life (HRQOL). A spine oncology-specific outcome measure has been developed by the Spine Oncology Study Group and validated through international studies. We proposed to tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Luksanapruksa et al 32 performed the translation and cross-cultural adaptation into Thai, and they reported that the domains pf the translated version maintained a high internal consistency (Cronbach alpha > 0.7) and that the questionnaire presented a strong correlation with the 5-Level EQ-5D (EQ-5D-5L). Likewise, Brodano et al 33 reported the validity of the Italian version in terms of the internal domains and their correlation with the SF-36 subdomains, as well as a high consistency among questionnaire items.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Luksanapruksa et al 32 performed the translation and cross-cultural adaptation into Thai, and they reported that the domains pf the translated version maintained a high internal consistency (Cronbach alpha > 0.7) and that the questionnaire presented a strong correlation with the 5-Level EQ-5D (EQ-5D-5L). Likewise, Brodano et al 33 reported the validity of the Italian version in terms of the internal domains and their correlation with the SF-36 subdomains, as well as a high consistency among questionnaire items.…”
Section: Discussionmentioning
confidence: 95%
“…Luksanapruksa et al 32 realizaram a tradução e adaptação transcultural para o tailandês, e demonstraram que os domínios da versão traduzida mantiveram uma alta consistência interna (alpha de Cronbach > 0.7), e que o questionário manteve forte correlação com as pontuações obtidas na versão de 5 níveis do EQ-5D (EQ-5D-5L). Da mesma forma, Brodano et al, 33 demostraram a validade da versão italiana tanto em relação aos domínios internos quanto à sua correlação com os subdomínios do SF-36, além da alta consistência entre os itens do questionário.…”
Section: Discussionunclassified
“…This 27-question survey covers six dimensions that include pain, mental health, social interaction, bowel and bladder function, physical activity and neurological function. To date, validated translations of the English SOSG-OQ2.0 are available in Italian, Thai, Chinese, Dutch, and German (23)(24)(25)(26)(27); the latter is used for our registry. The EuroQol-5 Dimensions Questionnaire (EQ-5D) is a well known and widely used tool of 5 questions covering 5 dimensions, namely ambulation, autonomy, activities of daily life, pain, and psychological situation.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…The SOSGOQ 2.0 had been cross-cultural translated into Italian, German, Thai, simple Chinese and Dutch. [5][6][7][8][9] Due to the cultural difference, a direct simple translation of the original questionnaire often can't guarantee similar measurement properties, and the rough translation may lead to bias to impact the validity of cross-cultural adaptation. Consequently, methodological considerations are important in crosscultural comparisons, the process of cross-cultural adaptation should be followed, as well as the measurement properties should be used to assess.…”
Section: Introductionmentioning
confidence: 99%